Student participation in peer interaction – Use of material resources as a key consideration in an open-ended problem-solving mathematics task - Moate, Josephine; Kuntze, Sebastian; Chan, Man Ching Esther (LUMAT: International Journal on Math, Science and Technology Education, 2021)
This study explores how students deal with material resources in their peer interaction when working in pairs in an open-ended problem-solving task. The productive use of material resources can be expected to support successful peer work. However, research into social phenomena in peer interaction is needed in order to identify and describe productive and less productive forms of dealing with material resources as students participate in open-ended problem-solving tasks. Consequently, this explorative study responds to this research need. Based on multimodal data, including video recordings, transcribed talk and the written contributions from four pairs of Year 7 students aged 12-13 years, the analysis focuses on different ways in which students deal with material resources while negotiating their participation as they respond to the task. The findings indicate that aspects of participation are a key factor for describing productive and less productive ways of dealing with material resources by the student pairs. Foregrounding aspects of participation for an increased awareness of potential obstacles to student-centred work is among this study’s contributions for classroom practice and theory development.